(untitled) (Medico Legal Update, 2021)
Background: Mishaps are one of the fifth driving reasons for death in industrialized and creating nations. Wounds emerging from mishaps are an expanding general medical issue. Mishaps are a noteworthy reason for dreariness and mortality in kids. Objectives: The present study was undertaken to find out the knowledge level of women regarding domestic accidents among children. Method: A descriptive comparative research design was used for the present study. A study sample of 100 care takers of under- five children (50 residing in rural area and 50 residing in urban area) were selected with help of purposive sampling method. Structured questionnaire was used to assess the knowledge and Likert scale was used to find out the attitude regarding first aid measures regarding selected domestic accidents among under five children. Results: In rural area maximum numbers of care takers had average knowledge regarding domestic accidents i.e. 74%, 22% had good knowledge and 4% had below average. Where as in urban area maximum numbers of care takers had average knowledge regarding domestic accidents i.e. 62%, 33% had good knowledge and 8% had below average. In rural area maximum numbers of care takers had undecided attitude regarding domestic accidents i.e. 64%, 36% had strongly disagree attitude and 0% had strongly agree attitude regarding statements. Where as in urban area maximum numbers of care takers had undecided attitude regarding domestic accidents i.e. 78%, 20% had strongly disagree attitude and 2% had strongly agree attitude regarding statements. Conclusion: The study findings concluded that majority of care takers have average knowledge and undecided attitude towards domestic accidents of under five children. So, the researcher provides the information booklet to enhance and improve knowledge and attitude of care takers towards domestic accidents.